2021
DOI: 10.3390/cells10061560
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Activation by Capsaicin Mediates Glucose Oxidation and ATP Production Independent of Insulin Signalling in Mouse Skeletal Muscle Cells

Abstract: Background: Insulin resistance (IR), a key characteristic of type 2 diabetes (T2DM), is manifested by decreased insulin-stimulated glucose transport in target tissues. Emerging research has highlighted transient receptor potential cation channel subfamily V member (TRPV1) activation by capsaicin as a potential therapeutic target for these conditions. However, there are limited data on the effects of capsaicin on cell signalling molecules involved in glucose uptake. Methods: C2C12 cells were cultured and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…Capsaicin acts through the activation of TRPV1, a calcium-permeable ion channel [1,44,45]. Many in vitro, animal, and human studies have confirmed the beneficial role of capsaicin in the modulation of glucose metabolism [1,3,7,12,19,46]. Similarly, zinc affects glucose homeostasis through various pathways, activating signalling molecules involved in glucose uptake and insulin action such as protein kinase B (AKT), small heterodimer partner (SHP), and extracellular signal-regulated protein kinases 1 and 2 (ERK1/2), in both healthy and diabetic individuals [2,4,5,8,15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Capsaicin acts through the activation of TRPV1, a calcium-permeable ion channel [1,44,45]. Many in vitro, animal, and human studies have confirmed the beneficial role of capsaicin in the modulation of glucose metabolism [1,3,7,12,19,46]. Similarly, zinc affects glucose homeostasis through various pathways, activating signalling molecules involved in glucose uptake and insulin action such as protein kinase B (AKT), small heterodimer partner (SHP), and extracellular signal-regulated protein kinases 1 and 2 (ERK1/2), in both healthy and diabetic individuals [2,4,5,8,15].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies on the importance of food components on glucose metabolism have highlighted capsaicin and zinc as potential therapeutic targets for carbohydrate metabolism diseases [1][2][3][4]. Capsaicin, the bioactive phenolic component of chilli peppers, has potential benefits in the reduction of glucose metabolism disorders and acts through the activation of transient receptor potential cation channel subfamily V member (TRPV1) [1,3]. Similarly, zinc plays an essential role in the prevention of carbohydrate metabolism diseases, and disruption in zinc homeostasis is strongly associated with the pathogenesis of these disorders [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations